Internal UHF antenna for partial discharge detection in GIS. Issue 14 (28th September 2018) - Bin, Feng; Wang, Feng; Sun, Qiuqin; Lin, Shu; Xie, Yaoheng; Fan, Min
Abstract : A compact ultra‐high‐frequency (UHF) antenna is developed in this work. First, by means of shifting symmetrical octagonal monopole into asymmetrical one, the impedance matching performance of antenna at high frequencies is improved; then, by cutting the radiation patch and ground plane in part, the antenna is reduced by 37.9% in size while maintaining its bandwidth; finally, a Γ‐shaped slot on the ground plane is utilised to create an additional resonance, decreasing the low cutoff frequency without enlarging the antenna volume. The proposed antenna only occupies 124 mm × 77 mm × 1.6 mm and achieves 3:1 voltage standing wave ratio from 575 MHz to more than 4.5 GHz, along with simple structure, good radiation patterns, moderate peak gain, and strong pulse handling capability. Furthermore, the electrical dimension, ratio bandwidth, and bandwidth dimension ratio are compared with those of existing broadband antennas. The partial discharge (PD) experiments have been carried out for four typical insulation defect models in gas‐insulated switchgear (GIS), and the results demonstrate that it is more sensitive to PD signals arising from floating metal, free metal particle, and void in the epoxy resin as compared to the disc coupler.